UPAYA KEMENPAREKRAF MENINGKATKAN KUNJUNGAN WISATAWAN MANCANEGARA MELALUI KEGIATAN GASTRO TOURISM 2019 DI BALI - Pratista, Devani Eka; Harini, Setyasih; Dipokusumo, GPH (Solidaritas, 2020)
Culinary is often used as a tourist attraction to invite the international community to be motivated to come to visit an area. Not a few people choose to visit an area with the aim of tasting the special foods and drinks found in that region. This is what is known as gastro-tourism or also known as culinary tourism. Gastronomic tourism is experiential travel to a gastronomic area, for recreational or entertainment purposes, which includes visits to primary and secondary food producers, gastronomic festivals, food exhibitions, events, cooking events and demonstrations, tasting quality food products or tourism activities related to food. The island of Bali is one of the small islands in the Indonesian waters which has a big impact on the world of tourism in Indonesia. There are also various and complete types of tourist attractions on the island of Bali, starting from the beach, rice fields, art and what are unforgettable are Balinese specialties. Bali is one of the favorite tourist destinations for tourists, especially foreign tourists. The attractiveness of Bali for tourists is not only its natural beauty, emalinkan its special food also has an attraction for tourists, especially foreign tourists. This study describes and analyzes the efforts of the Ministry of Tourism and Creative Economy in increasing foreign tourist visits through Gastro Tourism 2019 activities in Bali. In this activity, Ubud, Gianyar Bali Regency became an icon of World Gastronomy which was selected directly by a team of representatives from UNWTO who had been selected from 2017. The purpose of this paper is that this study aims to analyze whether the 2019 Gastro Tourism activities succeeded in attracting many foreign tourists who was in Bali to come to the event. The research method used by researchers is qualitative research using descriptive analysis method. Keywords: Gastro Tourism, Kemenparekraf, Bali